The triple bind of narration: Fritz Schütze’s biographical interview in prison research and beyond - Siebert, Sabina (2016)
In this article we re-evaluate Fritz Schütze’s biographical interview method with its orientation towards the analysis of social problems experienced by the individual. We used Schütze’s method in a study of repeat offenders in a Polish prison, and on the basis of this experience we believe that we make two contributions – one to social science enquiry in general, and one to prison sociology. We argue that in social science research this method offers unique insights into the process of identity formation. These insights are made possible because of the ‘triple bind of narration’ inherent in Schütze’s method, that is to say the requirement to close, the requirement to condense and the requirement to provide detail. In relation to prison research we argue that Schütze’s method has rehabilitation value in making the interviewee/narrator re-evaluate their life through biography work. We also offer practical advice on how to conduct such interviews